(3eSGFd hCLhHJgG aj Yde UfGYI GdcMds - (3OGfjGd Hf TYjGQs; (3GdcMGd , Ydj Hf YjSi GdWHjH GdcMGd,J (B400 (3g` ? s
(3ChdgG (B:s
(3gPG JYdjb (B( (3jMJhi (B) (3Ydi eSGFd hCLhHJgG ef JPcQI GdcMGdjf eG SeJg JPcQI GdcMGdjf eG bSeJgg KdGK ebGdGJ GdChdi jPcQ ajgG JTQjM GdYjf s
(3BNQgG (B:s
(3MQa GddGe Cda dGRhQO ebHV dWja cedJ eSGFd GdebGdI GdKGdKI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs